Association of maternal metal exposure and psychological status with adverse pregnancy outcomes: a nested case-control study - Du, Yunyun; Zhu, Jiashu; Wang, Chunyan; Zhang, Lingling; Wang, Hao; Yu, Zexin; Ma, Shuqin; Guan, Suzhen (Frontiers in Public Health, 2025)
BackgroundUncertainties persist regarding the relationship between serum metal concentrations, maternal mental health, and adverse pregnancy outcomes. This study investigated their impact on adverse birth outcomes to improve maternal-infant health.MethodsA nested case-control study was conducted involving 468 pregnant women. Data on demographics and mental health, focusing on pregnancy-related anxiety and familial adaptation, partnerships, growth, affection, and resolve, were collected. We measured maternal serum concentrations of nine metals and trace elements. Mediator equations were used to explore the roles of maternal metal exposure and mental health in adverse pregnancy outcomes, including preterm birth, low birth weight, and large-for-gestational-age.ResultsThere were statistically significant differences in serum concentrations of manganese (Mn), iron (Fe), nickel (Ni), and lead (Pb) between cases (n = 196) and controls (n = 272) (p < 0.05). Mn, Ni, and Pb exhibited positive linear dose-responses with adverse outcomes, while chromium (Cr) indicated a negative relationship. Pregnancy-related anxiety was a risk factor (Odds ratio = 1.041, 95% confidence interval: 1.002–1.083). Strontium (Sr) had a linear relationship with pregnancy-related anxiety, whereas the other variables exhibited nonlinear associations. Maternal psychological status during pregnancy showed no mediating effect the associations between maternal exposure to Cr, Fe, Ni, and Pb and adverse pregnancy outcomes.ConclusionThe findings suggest that elevated maternal serum levels of Mn, Ni, and Pb, coupled with diminished Cr levels and increased pregnancy-related anxiety, were associated with risks of adverse pregnancy outcomes. This study establishes critical links and provides a basis for preventive strategies aimed at improving maternal and infant health.